The Dynamics of Training Outcomes in a Training Experience - Chong, Siaw Fung; Peter, Songan (Faculty of Cognitive Sciences & Human Development,UNIMAS, 2016)
It is rather common to find researchers and practitioners in training and development evaluating training effectiveness based on Kirkpatrick’s criteria of training reactions, learning, behavior change, and overall results. In recent years, in-depth review of Kirkpatrick’s criteria for training evaluation by theorists and researchers resulted in renewed interest in possible underlying dimensions and more operationalized measures of these factors. In this study, a hypothesized model is proposed to explain the effects of training reactions on learning outcomes and training transfer. Path analysis is carried out on data collected from 118 participants of a training course on operational housekeeping to examine the validity of the proposed model. Training reactions is considered in terms of affective reactions and utility reactions, and learning is considered in terms of declarative learning and application-based learning. Moderate effects between affective reactions, declarative learning, and training transfer are observed; while the links between affective reactions and utility reactions, and between declarative learning and application-based learning appeared to be more significant.